The greatest stories never told : 100 tales from history to astonish, bewilder, & stupefy - Beyer, Rick, 1956-; History Channel (Television network) (New York : HarperResource, 2003)
A collection of historical facts includes the Pilgrims' decision to land in Plymouth because they ran out of beer, the invention of the stethoscope by a modest French doctor, and the development of the first fax machine in 1863
Based on the television program: Timelab 2000.
Includes bibliographical references (p. 200-208).
Keywords: History -- Anecdotes; Historia -- Anécdotas